Total aset, jaringan kantor, sumber daya manusia dan kinerja perbankan syari’ah sebelum dan selama pandemi Covid 19 di Indonesia : analisis perbandingan - Citarayani, Irma (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine whether there are differences in the value of Total Assets, Number of Office Networks, Number of Workers and Return On Assets at Islamic Commercial Banks before the Covid 19 Pandemic and during the Covid 19 Pandemic. The type of data used in this research is quantitative data and is secondary data in the form of monthly time series (time series). The data was obtained from the official website of the Financial Services Authority (OJK) through Sharia Banking Statistics from January 2019 – April 2021 (14 periods before the Covid 19 Pandemic and 14 periods before the Covid 19 Pandemic). The research method used in this research is descriptive and comparative analysis method, which is a method to see a comparison between the conditions of a variable or more in two or more different samples, or at two different times. The data processing was carried out using SPSS software. The results showed that there was a difference in the value of Total Assets, Number of Office Networks, and Return On Assets before the Covid 19 Pandemic and during the Covid 19 Pandemic, while the value of the Number of Workers did not have a difference between before and during the Covid 19 Pandemic.